Effect of the time-point of acid etching on the persistence of sealer residues after using different dental cleaning protocols - Jordão-Basso, Keren Cristina Fagundes; Kuga, Milton Carlos; Bandéca, Matheus Coêlho; Duarte, Marco Antonio Hungaro; Guiotti, Flávia Angélica (FapUNIFESP (SciELO), 2016)
Endodontic sealer residues remaining within the pulp chamber dentin after root canal obturation and cleaning with various solvents may compromise the appearance and the durability of dental restorations. Acid etching is routinely performed prior to application of dentine adhesive systems, but is effect on residual sealer material and the optimal time-point for performing etching, are unknown. Here, we evaluated the effect of acid etching on the dentin surface when performed either immediately or 7 days after removal of the endodontic sealer with two solvents, i.e., 95% ethanol or xylol. Forty crowns fragments from bovine incisors were impregnated with sealer and divided into 4 groups (n = 10 each), according to the dentin cleaning protocol and to the acid etching time-point: G1, 95.0% ethanol and immediate acid etching; G2, xylol and immediate acid etching; G3, 95.0% ethanol and acid etching after 7 days; and G4, xylol and acid etching after 7 days. Scanning electron microscopy (SEM) images (2000 ×) were obtained from each specimen and the number of open dentinal tubules counted and compared. Another 40 fragments were similarly prepared, and SEM images were obtained (500 ×) to score and compare the persistence of sealer residues on the dentin. G4 showed the most open dentinal tubules and the least epoxy resin-based sealer residues on the dentin surface (p < 0.05). The least epoxy resin-based sealer residues was obtained when acid etching, using 37% phosphoric acid, was performed after 7 days after cleaning the dentin with xylol.